A method for selecting P antigen-negative red cell units for patients with paroxysmal cold hemoglobinuria - Geethika Sajeewani Manchanayake (Asian Journal of Transfusion Science)
In the absence of specific antisera and molecular typing technique, selection of P antigen-negative red cell unit is a challenge. This article explains a new technique that can be used in emergency situations to screen P antigen-negative red cell unit for the transfusion of patients with paroxysmal cold hemoglobinuria tested positive for Donath-Landsteiner antibody. The technique is based on the theory behind the Donath-Landsteiner test, and it can be performed even in a transfusion laboratory with minimum facilities.